The Effect of Online Written Feedback Through Social Media on Student’s Writing - Rona Elfiza; Aninda Sri Reszki; Dewi Nopita (J-SHMIC : Journal of English for Academic, 2021)
Writing is considered as a hard language skill for students. English teachers have been trying to find the effective way to enhance their students’ writing skill. One of them is providing feedback in students’ written work, also known as written Feedback. This article retrieved from the research on the effect of online written feedback through social media on students’ writing in SMAN 4 Tanjungpinang. This research aims to find out the effect of Online Written Feedback on students’ writing skill through social media Facebook at SMAN 4 Tanjungpinang. A pre-experimental design with one group pre-test-post-test was used in this research. There were 30 eleventh grade students of SMAN 4 Tanjungpinang as the sample of the research. This research used written assignment as its instrument. A pre-test is administered at the beginning of the research and followed by providing online written feedback on students’ writing personal letter as the treatment. A post-test was also conducted after the treatment. The pre-test and post test scores were analysed by using a paired sample t-test to answer the research hypothesis. This research showed that online written feedback did not significantly affect the students’ writing skill in SMAN 4 Tanjungpinang. There was a difference between the mean score of pre and post-test, from 83.07 to 85.70, but it was not significantly.